What are the Effective Factors in Spontaneous Resolution Rate of Primary Vesicoureteral Reflux: A Meta-Analysis and Systematic Review - Basiri, Abbas; Ziaeefar, Pardis; Khoshdel, Alireza; Fattahi, Payam; Mafi Balani, Mohammadreza; Tofighi Zavareh, Mohammad Amin (Urology Journal, 2023)
Purpose: This meta-analysis aimed to predict the rate of spontaneous resolution and identify influencing factors among pediatric patients with primary vesicoureteral reflux (VUR). The primary objective was to construct a nomogram to facilitate clinical decision-making in the treatment of primary VUR by assessing the rate of spontaneous resolution and its determinants. Materials and Methods: A systematic search was conducted up to September 2023, encompassing databases such as PubMed, Web of Science, Scopus, and the reference lists of relevant studies. Inclusion criteria comprised 33 studies with a total of 8540 pediatric patients. Data extraction was performed independently by two reviewers, with discrepancies resolved by a third reviewer. Risk of bias was assessed using the Newcastle-Ottawa Quality Assessment Form. The analysis included the assessment of various outcomes, such as the rate of spontaneous resolution, and identification of influential factors, including gender, age, laterality, and VUR grade. Results: The pooled spontaneous resolution rate among pediatric patients with primary VUR was 0.42 (95% CI: 0.38 to 0.47, Tau2 = 0.26), demonstrating high heterogeneity (Q = 429.9, df = 32, P < 0.001, I2 = 93%). Egger’s regression test indicated no publication bias (p = 0.67). VUR grade emerged as the most significant determinant of spontaneous resolution, with varying rates for different grades: grade 1 (0.80, 95% CI: 0.72-0.86), grade 2 (0.67, 95% CI: 0.60-0.74), grade 3 (0.49, 95% CI: 0.42-0.56), and grade 4 (0.23, 95% CI: 0.18-0.30; Tau2 = 0.28, I2 = 0.49). While differences in gender and laterality were observed, statistical significance was not evident. Conclusion: This study provides valuable insights into the spontaneous resolution rate of primary vesicoureteral reflux in pediatric patients. The constructed nomogram, based on VUR grading, serves as a useful tool for clinicians in decision-making. Despite observed variations in gender and laterality, only VUR grading demonstrated statistical significance in influencing spontaneous resolution. Further research is recommended to explore additional factors within larger populations to enhance our understanding of primary VUR resolution dynamics.